Improved resistivity and surface morphology of laser treated Cr/Pd metal contact sputter deposited on Si - Ahmad, Rabiatul Adawiah; Ali, Ahmad Hadi; Isiyaku, Aliyu Kabiru; Bhari, Bibi Zulaika (UTHM Publisher, 2017)
In this paper Cr/Pd metal contacts were deposited on Si by using DC magnetron sputtering. The metal contacts were treated using infrared Nd:YAG pulsed laser at different laser pulse energy. The metal contacts were characterized based on electrical, optical and morphology properties by using four-point probes, ultraviolet-visible spectroscopy (UV-Vis) and atomic force microscope (AFM). Measurement obtained from four point probes shown lowest resistivity values for post treatment sample after treated with 25 mJ laser pulsed energy. The measured value is 6.75 × 10-5 Ohm-cm as compared to the as-deposited sample of 1.060 × 10-4 Ohm-cm. The scanned data using UV-Vis shown the characteristics of the thin metal contacts to absorbing light spectrum, whereas reflect light in visible wavelength range. Meanwhile, AFM results confirmed the post-treatment sample has smoother surface as compared to the as-deposited sample.